PENGARUH PERSEPSI HARGA, PROMOSI PENJUALAN, DAN CITRA MEREK TERHADAP KEPUASAN UNTUK MENINGKATKAN LOYALITAS PELANGGAN - Suastini, Ida Ayu Komang Sri; Mandala, Kastawan (E-Jurnal Manajemen; Vol 8 No 1 (2019), 2019)
This research would like to explain the influence of price perception, sales promotion, and brand image to satisfaction to increase customer loyalty. This study was conducted in Denpasar City involving 105 respondents by using purposive sampling as a method in sampling. Data collection is done by distributing questionnaires containing statements relating to the variables of price perception, sales promotion, brand image, customer satisfaction and customer loyalty. Furthermore, data from the results of collecting the questionnaire is processed by using the validity test, and reliability test to determine the feasibility and consistency of indicators in the questionnaire. The analysis technique used in this research is path analysis and Solimun theory. The results of this study found that the perception of prices, sales promotion, and brand image have a positive and significant impact on customer satisfaction. Customer satisfaction has a positive and significant influence on customer loyalty.